Employment and the Buying Power of Consumers - Berridge, W. A. (The Review of Economics and Statistics, 1930)
R ARELY if ever has there appeared more widespread interest in employment and other measures of wage earners' economic status than in this depression of I930. Rather belatedly, employment is being looked upon with keen interest, not in its industrial and its social aspects alone, but especially in its relation to commercial problems the flow of money income and of commodity purchasing power, and the prospects for recovery in the wage-earner market for consumers' goods, especially those produced by mass methods. For some years past, a high level of gold wages, coupled with a relatively low cost of subsistence, had maintained the standard of real or commodity buying power at well-nigh unprecedented heights. This in turn helped to foster and further the consumption of mass-produced goods the production of which, under rising standards of industrial efficiency, had made possible the very existence of this high-wage era. But the benefits of all this (like many other human blessings) were not fully appreciated by some of the parties having most at stake the trade interests -until these benefits began to be taken away by the ruthless hand of business depression. In various published forms, including several issues of this REVIEW,I scattered over the last nine years, we have attempted to lay a technical groundwork, comprising a descriptive statement of the statistical operations performed, together with an analytical discussion of the technical problems involved, in the development of various indexes reflecting cyclical movements in labor conditions. We hope that this fundamental work has been done with sufficient thoroughness to justify our devoting comparatively little attention to technical matters in the present article. Therefore we confine ourselves to a portrayal of the leading economic facts on the subject, statistically measured, of course, but accompanied by no more discussion of statistical methodology than is necessary.